Clinical validity of fluorescence-based devices versus visual-tactile method in detection of secondary caries around resin composite restorations: diagnostic accuracy study - Aya Mohamed Adly; Shereen Hafez Ibrahim; Amira Farid El-Zoghbi (BDJ Open)
Abstract Objectives To assess the validity of light-induced and laser-induced fluorescence devices compared to the visual-tactile method for detecting secondary caries around resin composite restorations. Materials and Methods The study included 20 participants with 30 resin-composite restored teeth. Restorations’ margins were examined using three diagnostic methods: the visual-tactile method (FDI criteria), the light-induced fluorescence camera (VistaCam iX), and the laser-induced fluorescence device (DIAGNOdent pen), and the reference was visual inspection after removal of defective restorations. The validity of each method was evaluated. Inter-examiner reliability was calculated using Cohen’s kappa statistics. The level of significance was set at P = 0.05. Results DIAGNOdent pen showed the highest sensitivity (100%) followed by VistaCam (98.82%) and the visual-tactile method (98.82%) at the enamel threshold. DIAGNOdent pen and VistaCam had lower specificity values than the visual-tactile method (81.69%, 76.06%, and 88.73% respectively). At the dentin threshold, DIAGNOdent pen yielded the highest sensitivity (89.36%), whereas VistaCam had the lowest (8.51%). The sensitivity of the visual-tactile method was low (57.45%) whereas all diagnostic methods had high specificity. There was perfect agreement in inter-examiner reliability for all assessment methods (Kappa 0.858–0.992). Conclusions Both fluorescence-based devices and the visual-tactile method are reliable for detecting secondary caries around resin composite restorations. DIAGNOdent pen is accurate in enamel and dentin, while VistaCam and the visual-tactile method can detect secondary caries in enamel only. Clinical Relevance Fluorescence-based devices could be used as a valuable aid to supplement or as a second opinion after the visual-tactile method. Trial registration The study was listed on www.clinicaltrials.gov with registration number (NCT04426604) on 11/06/2020.